In search of a local palaeoenvironmental record: combining archaeobotany and stable carbon isotopes to investigate life, occupation patterns and water stress at the epipalaeolithic site of Kharaneh IV in the Azraq Basin, Jordan - Bode, Leslie Jennifer Kate (2018)
This thesis employs two approaches to investigate water stress at the early and mid Epipalaeolithic site of Kharaneh IV in the Azraq Basin, Jordan. Firstly, the archaeobotanical analysis explores the local environment by using the ecology of identifiable charred seeds to indicate water availability (autoecology). Included alongside this is a seed catalogue, which presents the unique archaeobotanical assemblage recovered through sampling. Secondly, to further explore the local palaeoenvironment and due to the potential broad hydrological tolerances of some species, stable carbon isotope δ13C analysis of the archaeobotanical remains is used to track changes in water stress during the occupation of the site. These analyses provide a complementary approach to traditional archaeobotanical studies. Combined, these data offer considerable insight into questions about the local environment, particularly water stress, and the potential use of plants during the occupation of Kharaneh IV. The results presented here demonstrate that Kharaneh IV experienced variable water stress throughout its occupation, with a drying out of the site coincident with the end of occupation. This signature of drying is found within both the isotopic and autoecological analyses, providing multiple lines of evidence for this pattern. This thesis serves as a case study for the usefulness and inferential power of multi-method approaches that combine archaeobotanical and isotopic analysis.